Permission to Parent : How to Raise Your Child with Love and Limits - Berman, Robert E, 1950- (HARPER WAVE, 2014)
Based on her clinical experience, a psychiatrist presents a valuable guide that helps parents and children navigate the emotional and psychological minefields of family dynamics.